2008
DOI: 10.1007/s11747-008-0117-x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility: attributions, loyalty, and the mediating role of trust

Abstract: This study investigates whether consumers' perceptions of motives influence their evaluation of corporate social responsibility (CSR) efforts. The study reveals the mediating role of consumer trust in CSR evaluation frameworks; managers should monitor consumer trust, which seems to be an important subprocess regulating the effect of consumer attributions on patronage and recommendation intentions. Further, managers may allay the negative effects of profit-motivated giving by doing well on service quality perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
635
4
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 673 publications
(720 citation statements)
references
References 41 publications
(60 reference statements)
30
635
4
9
Order By: Relevance
“…Research has shown that customers prefer products from companies involved in social causes (García de los Salmones et al, 2005, p. 373). Customers have more trust, purchase more, and prefer to recommend socially responsible companies (Vlachos, Tsamakos, Vrechopoulos, & Avramidis, 2009). Numerous studies have shown a positive relationship between perceptions of CSR and customer loyalty (Ailawadi, Neslin, Luan, & Taylor, 2014;Chung et al, 2015;García de los Salmones et al, 2005;He & Li, 2011;Lee et al, 2012;Marin et al, 2009;Perez et al, 2012;Srbljinović, 2012).…”
Section: Economic Responsibilitiesmentioning
confidence: 99%
“…Research has shown that customers prefer products from companies involved in social causes (García de los Salmones et al, 2005, p. 373). Customers have more trust, purchase more, and prefer to recommend socially responsible companies (Vlachos, Tsamakos, Vrechopoulos, & Avramidis, 2009). Numerous studies have shown a positive relationship between perceptions of CSR and customer loyalty (Ailawadi, Neslin, Luan, & Taylor, 2014;Chung et al, 2015;García de los Salmones et al, 2005;He & Li, 2011;Lee et al, 2012;Marin et al, 2009;Perez et al, 2012;Srbljinović, 2012).…”
Section: Economic Responsibilitiesmentioning
confidence: 99%
“…Attributing a stakeholder-driven motivation to CV activities reflects the belief that a company engages in CV to satisfy the expectations of different stakeholders (shareholders, employees, society) (Vlachos et al, 2009). Some argue that companies are responsive to stakeholders out of necessity (Skarmeas and Leonidou, 2013) and only because stakeholders pressure them into such behaviour (Groza, Pronschinskee and Walker, 2011).…”
Section: H1mentioning
confidence: 99%
“…Previous research on the effects of CSR on financial performance mostly focused on the product-based industry (Kang et al, 2010;Vlachos et al, 2009). We investigate whether and how this relationship may be particularly important in the service-selling context.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 99%